2022
DOI: 10.13057/biodiv/d230315
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of wild edible fruit plant species and their threatened status in the Aceh Province, Indonesia

Abstract: Abstract. Suwardi AB, Navia ZI, Harmawan T, Seprianto, Syamsuardi, Mukhtar E. 2022. Diversity of wild edible fruit plant species and their threatened status in the Aceh Province, Indonesia. Biodiversitas 23: 1311-1319. Aceh Province, Indonesia is home to a diverse range of tropical fruit plants. However, increased anthropogenic activities such as population growth and natural disasters resulted in various biological resources such as wild edible fruit plants being under threat. The study aimed to assess the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…It was discovered during discussions with respondents that many children were interested in learning medicinal plants from healers or elders in their village. This is in line with a study on medicinal plants in the Aneuk Jamee tribe, where the younger generation learns a lot of medicinal plants from their parents (Suwardi et al 2022a).…”
Section: The Threat Of Wild Medicinal Plantssupporting
confidence: 85%
See 1 more Smart Citation
“…It was discovered during discussions with respondents that many children were interested in learning medicinal plants from healers or elders in their village. This is in line with a study on medicinal plants in the Aneuk Jamee tribe, where the younger generation learns a lot of medicinal plants from their parents (Suwardi et al 2022a).…”
Section: The Threat Of Wild Medicinal Plantssupporting
confidence: 85%
“…For example, a study by Setiawati et al (2016) found that many plants in the forest contain substances with pharmacological properties and bioactivity that can be utilized to cure mild, serious, and degenerative disorders, as well as cancer. The high diversity of plants is also important in terms of cultural aspect (Silalahi 2016;Sutrisno et al 2020), as well as for the provision of food (Navia et al 2020b;Sutrisno et al 2021;Syamsuardi et al 2022;Ramaidani and Navia 2022;Suwardi et al 2022a), fuelwood, construction material and fodder (Elfrida et al 2020;Noverian et al 2020;Navia et al 2020a;Suwardi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…4 WEFs are still consumed by a large section of global population in the remote/ rural places as affordable food with incomparable source of nutritional security. 5,6 WEFs are nutrient-dense sources of vitamins, minerals, antioxidants and serve as a vital source of food, and healthcare among rural people in the remote. 4 Ethnic groups across the world are known for their indigenous cultures, customs, religious rituals, myths, medicine, food and many other folklore practices that are largely unique and endemic to a particular region.…”
Section: Introductionmentioning
confidence: 99%
“…Mangrove forests can store carbon four times more than other vegetation ecosystems because the carbon stocks absorbed in mangrove stands are stored in the form of biomass [7]. Mangrove ecosystems could store carbon stocks of 241.38 tons/ha [8].…”
Section: Introductionmentioning
confidence: 99%